A convenient synthesis of phthalocyanines bearing four methyl 4-hexyloxyphenyl-2-phenoxy acrylate functionalities - (:unkn) unknown (WORLD SCI PUBL CO INC, 2009)
A novel synthetic pathway for the preparation of a new phthalonitrile derivative, methyl (E)-3-[2-(3,4-dicyanophenoxy)-4-(hexyloxy) phenyl] acrylate (3), based on the opening of the lactone ring of 7-hexyloxycoumarin (2H-1-benzopyrane-2-one, 2H-chromen-2-one) and ether formation of the formed hydroxy group with 4-nitrophthalonitrile, is presented. Cyclotetramerization of this dinitrile in 2-N,N-dimethylaminoethanol gives the desired Zn(II), Co(II) and Cu(II) phthalocyanines (4, 5 and 6) with four methyl 4-hexyloxy-2-phenoxy acrylate moiety on periphery. The complexes are characterized by IR, elemental analysis, H-1 NMR, C-13 NMR MALDI-TOF and UV-vis spectroscopy. The redox behavior of the complexes are also discussed.
Keywords: 7-hydroxycoumarin (umbelliferone); phenyl acrylate; metallophthalocyanines; electrochemistry; METAL-FREE; ELECTROCHEMICAL PROPERTIES; SUBSTITUENTS; COMPLEXES; DERIVATIVES; LIGAND